Positive and Negative Control of R-Factor Replication in Proteus mirabilis - Punch, J. D. (1972)
Replication of the 50 and 58 moles per cent guanine plus cytosine (%GC) components of R factor 222 in Proteus mirabilis during growth in the presence and absence of chloramphenicol and after shifting exponential- and stationary-phase cells to conditions which inhibit host protein or deoxyribonucleic acid (DNA) synthesis was examined. Chloramphenicol reduced the growth rate but increased the amount of both R-factor components; the 58% GC component showed a larger proportionate increase. This was inferred to indicate reduced synthesis of an inhibitor that acts on both R-factor components and an initiator for replication of the 50% GC component. Replicative patterns observed after shifting exponential- and stationary-phase cells grown with or without chloramphenicol to minimal medium or chloramphenicol for one generation, or puromycin for 3 hr, corroborated this interpretation. After shifts of exponential cells from either medium, replication of the 50% GC components paralleled host replication, thus indicating a requirement for protein synthesis; replication of the 58% GC component increased due to reduced inhibitor synthesis. R-factor DNA remained constant after shifting stationary cells from drug-free medium, thus indicating that the cells contained effective concentrations of the regulatory inhibitor, whereas increased replication of the 58% GC component occurred after identical shifts of chloramphenicol-grown cells of the same chronological age. Similar responses were observed after shifts to 5 C or to medium containing streptomycin or tetracycline. Absence of replication of the 50% GC component after shifting to medium containing nalidixic acid or phenethanol and its hereditary persistence during growth indicated that the 50% GC replicon was attached to the membrane. Thus, in P. mirabilis the three replicons of R factor 222 are regulated as follows: The composite and transfer portion (RTF) replicons represented by the 50% GC component require protein synthesis and membrane attachment and are negatively regulated by an inhibitor; the 58% GC or resistance-determinants replicon exists cytoplasmically and is subject only to negative control.